PRACTICAL ASPECT OF APPLICATION THE RESOURCE MANAGEMENT OPTIMIZATION MODEL IN CIRCULAR ECONOMY CONDITIONS - Lema, H. V.; Siaryi, I. V. (The actual problems of regional economy development, 2024)
The article analyzes the peculiarities of the circular economy as an element of sustainable development of the environment. In particular, the author analyzed the views of scientists in the field of circular economy of various business entities. A comparative characterization of the types of economy, namely: circular economy, green economy and linear economy. It was determined that the circular economy involves a transition from simply owning goods to providing services that can reduce resource consumption. This concept is becoming more and more relevant in the conditions of growing awareness of the problems of environmental pollution and the limitation of natural resources. Many countries and companies are actively developing and implementing circular economy strategies to reduce their environmental impact and create more sustainable economic models. Such an approach can help businesses ensure greater resilience in changing conditions and maintain competitive advantages in the market for several reasons: reducing dependence on limited resources, reducing organizational costs, stimulating innovation, reducing risks from changes in the environment, etc. Taking into account the problems with the effective use of resources, which are important in the conditions of the circular economy, and which are necessary for the development of domestic enterprises, it is advisable to use optimization models. Optimization models allow efficient management of resources and production processes, maximizing the use of resources and reducing losses. The basis of the optimization model is the objective function and constraints, which take into account various aspects of the enterprise's activity. The objective function in an optimization model can be aimed at maximizing a certain metric, such as profit or resource utilization, or at minimizing costs or environmental impact. Such an approach not only contributes to the achievement of greater efficiency and competitiveness of enterprises, but also contributes to their sustainable development, as it takes into account not only economic, but also social and environmental aspects. Therefore, the transition to a circular economy can become a key strategic step for business, helping to maintain competitive advantages and ensure sustainable development in unpredictable conditions.